PENINGKATAN PERTUMBUHAN BIBIT OKULASI KARET ( Havea brasilliensis Mull arg) KLON ANJURAN DI POLIBEG DENGAN PPC - Joko Supriyanto; Yardha . (Jurnal Agroekoteknologi, 2010)
ABSTRACT Rubber is forest commodity which planted most in Jambi with total area of 558.570 ha (97 % of community’s forest) and most are very old plants. Regeneration in commercial level has been done, however the quality of seedling was doubtful. Formers have their own preferency on superior clone of rubber such as PB260, RRIC100, and BPM24 but growth characteristics of those clones were not very well known yet. Thertore, research on growth of suggested clones need to be done done with optimal application of fertilizer research was conducted at trial plot of BPTP Jambi from May to November 2008. The experimental design was Completelty Randomized Design (CRD) with factorial assessed factory were : (1) Suggessted clone of rubber consist of A1 (BPM24), A2 (RRIC100), A3 (PB260) and (2) concentration of PPC Bayfolan consist of 5 lenels : Bo (Control), B1 (1,5 ml L-1), B2 (1,5 ml L-1), B3 (3 ml L-1), B4 (4,5 ml L-1), B5 (4,5 ml L-1). Parameters abserved were apical, langth, dry meight of roots, dry meight of apical, leaf total width, and quality index. Results shomed that there was in feraction betueen apical leugth and dry meight of apical, the highest yield was tahen from combination of A2B2. Parameters of root dry weight, leaf total width and quality index pave significanthy effect, RRIC100 gone the highest volume. PPC Bayfolan 3mll-1 gove the best yield. In overall, clone treatments gone significant effect on growth of seedling in the polibags while effect of PPC bayfolan shomed that there was optimum concentration on each suggested clone.Keywords: Seedling Grafting Rubber, Havea brasilliensis Mull arg, superior clone, PPC